Analysis of the nonlinear dynamic behavior of longitudinal systems in heavy-haul trains - Leiting Wang; Yang Jin; Wangxiang Li; Chenyang Tang (Electronic Research Archive)
The payload, coupler slack, and buffer device performance in heavy-haul trains substantially affect their longitudinal dynamic systems under operational conditions. These factors result in the bifurcation of the system, consequently leading to chaos. To study this phenomenon in depth, a two-degrees-of-freedom longitudinal dynamics model of the train is established. The system is analyzed using the fourth-order Runge–Kutta (R-K_4) numerical integration method, incorporating bifurcation diagrams, phase planes, Poincaré mapping, and time-domain analysis to elucidate the trajectory of the system as it transitions into a chaotic state of motion via period-doubling bifurcations and quasi-periodic motions. A comprehensive analysis of the complex nonlinear dynamics of the train's longitudinal system can establish a theoretical foundation for forecasting and regulating the chaotic motion of the train system.